Impacts of sea ice on suspended sediment transport during heavy ice years in the Bohai Sea - Liu, Siyu; Li, Guangxue; Liu, Shidong; Zhang, Lei; Li, Mengqi; Feng, Qi; Xing, Lvyang; Yu, Di; Pan, Yufeng (Frontiers in Marine Science, 2024)
The Bohai Sea, known for being the lowest latitude seasonally frozen sea area in the world, experienced severe ice conditions with a 30-year recurrence period during the winter of 2009-2010. Water-sediment flux is a crucial parameter for water quality management in marine environment. Using a highly accurate three-dimensional hydrodynamic and sediment transport numerical model, the significant wave height (Hs), current velocity, suspended sediment concentration (SSC) and water-sediment flux in the Bohai Sea during ice-covered and ice-free conditions are compared. Our findings indicate that the current velocity and sediment resuspension decrease under the ice coverage, but increase at the edge of the ice. The net outflow tidal flux (TF) in winter under ice-free conditions accounts for 24.5% of the whole year. The net outflow TF increases by 32.7% during ice-covered conditions, primarily due to the pressure difference between high air pressure superimposing heavy sea ice in the northwest Bohai Sea and the low air pressure in Bohai Strait, resulting in increased ebb velocity and decreased flood velocity. The net outflow suspended sediment flux (SSF) during ice-free conditions in the winter is 2.32×109 kg, while SSF increases by 1.24 times during ice-covered conditions, leading to worse water quality in the outer sea. The decrease of TF in the southern part of the Bohai Strait and the reduction of suspended sediment concentration by nearly 15 mg/l lead to the significant decrease in SSF. This study has significance guiding value for understanding the source-sink sedimentation system and water quality research in East China Sea.